Cyber Searches. - Adair, David N. (Federal Probation, 2001)
The potential for uncovering incriminating information through computer searches is tantalizing; however there is no justification for accepting that an offender's computer is more accessible to a probation officer than his or her physical property. There are constitutional and statutory limitations to conducting computer searches, and until such time as there is more clarity on these issues, probation officers should limit recommendations for search conditions in computer-related cases.